Locked posterior fracture-dislocation of the shoulder - Branca Vergano , Luigi; Landi, Stefano; Monesi, Mauro (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the work: To describe a valid option for the treatment of locked posterior fracture-dislocation of the shoulder (LPFDS) and to compare it to the literature about this topic. Methods: We present a small case series (3 patients), with a medium follow up at 4 years and 5 months. We accurately describe our surgical strategies, underlining the choice of approach, reduction and fixation. Results: The three patients showed excellent functional and radiological results at the follow up examinations, with a full range of shoulder movements and complete regain of pre-trauma activities. A lateral approach (standard or minimally invasive), a reduction technique with a Shantz pin in the head and in the humeral shaft, and fixation with a locking plate were used in the three patients. Conclusion: LPFDS is a challenging lesion, hard to recognize and to treat. Our suggested method of treatment is highly reproducible and has revealed itself to be very effective in achieving good results.